The genetic association with injury risk in male academy soccer players depends on maturity status. (18th October 2021) - Hall, Elliott C. R.; Baumert, Philipp; Larruskain, Jon; Gil, Susana M.; Lekue, Josean A.; Rienzi, Edgardo; Moreno, Sacha; Tannure, Marcio; Murtagh, Conall F.; Ade, Jack D.; Squires, Paul; Orme, Patrick; et al.
Abstract : It is currently unknown if injury risk is associated with genetic variation in academy soccer players (ASP). We investigated whether nine candidate single nucleotide polymorphisms were associated (individually and in combination) with injury in ASP at different stages of maturation. Saliva samples and one season's injury records were collected from 402 Caucasian male ASP from England, Spain, Uruguay, and Brazil, whose maturity status was defined as pre‐ or post‐peak height velocity (PHV). Pre‐PHV COL5A1 rs12722 CC homozygotes had relatively higher prevalence of any musculoskeletal soft tissue (22.4% vs. 3.0%, p  = 0.018) and ligament (18.8% vs. 11.8%, p  = 0.029) injury than T‐allele carriers, while VEGFA rs2010963 CC homozygotes had greater risk of ligament/tendon injury than G‐allele carriers. Post‐PHV IL6 rs1800795 CC homozygotes had a relatively higher prevalence of any (67.6% vs. 40.6%, p  = 0.003) and muscle (38.2% vs. 19.2%, p  = 0.013) injuries than G‐allele carriers. Relatively more post‐PHV EMILIN1 rs2289360 CC homozygotes suffered any injury than CT and TT genotypes (56.4% vs. 40.3% and 32.8%, p  = 0.007), while the "protective" EMILIN1  TT genotype was more frequent in post‐ than pre‐PHV ASP (22.3 vs. 10.0%, p  = 0.008). Regardless of maturity status, T‐alleles of ACTN3 rs1815739 and EMILIN1 rs2289360 were associated with greater absence following ankle injury, while the MMP3 rs679620 T‐allele and MYLK rs28497577 GT genotype were associated with greater absence following knee injury. The combination of injury‐associated genotypes was greater in injured vs. non‐injured ASP. This study is the first to demonstrate that a genetic association exists with injury prevalence in ASP, which differs according to maturity status.